2011
DOI: 10.1016/j.rmed.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Short terms effects of air pollution from biomass burning in mucociliary clearance of Brazilian sugarcane cutters

Abstract: Nasal mucociliary system is the first line of defense of the upper airways and may be affected acutely by exposure to particulate matter (PM) from biomass burning. Several epidemiologic studies have demonstrated a consistent association between levels of air pollution from biomass burning with increases in hospitalization for respiratory diseases and mortality. To determine the acute effects of exposure to particulate matter from biomass burning in nasal mucociliary transport by saccharin transit time (STT) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 14 publications
0
24
0
4
Order By: Relevance
“…Em um estudo realizado no campo de trabalho com cortadores de cana-de-açúcar, mostrou-se que a exposição aguda de quatro horas ao material particulado advindo da queima de biomassa foi responsável pela alteração do mecanismo de defesa respiratório desses trabalhadores 17 .…”
Section: Discussionunclassified
“…Em um estudo realizado no campo de trabalho com cortadores de cana-de-açúcar, mostrou-se que a exposição aguda de quatro horas ao material particulado advindo da queima de biomassa foi responsável pela alteração do mecanismo de defesa respiratório desses trabalhadores 17 .…”
Section: Discussionunclassified
“…Where sugarcane is grown and processed, the population has suffered from constant burning in the fields 27 , which increases the release of air pollutants, responsible for various health problems 41,42 . Ribeirão Preto has been heavily affected by this problem in recent decades, not only due to burning in sugarcane fields, but also by fires set by the residents themselves, who believe that burning fallen leaves and branches and the weeds growing on and around their lots, or even household garbage, will solve the problem of accumulated waste around their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Both fine and heavier particles can accumulate in the respiratory system, while the thicker particles can aggravate preexisting respiratory problems, especially in children and elderly, increasing the risk of emergency hospitalization and premature death 22,23 . In this context, various studies have shown that the release of gases from burning organic matter increases the incidence of respiratory and cardiovascular diseases, and that substances resulting from burning of sugarcane contribute to the incidence and increase of respiratory tract diseases 18,23,24,25,26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…A study has shown that acute exposure to sugarcane burning causes decreased mucociliary transport time in workers 9 . However, long-term effects are expected to increase mucociliary transport time 10 and decrease lung function 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is very important to know the effects of atmospheric pollutants, which can affect both MC and lung function, eventually leading to an increase in lung diseases and nasal symptoms 7,[9][10][11] . The aim of this study was to evaluate the effects of sugarcane burning on sugarcane workers' lung function and mucociliary clearance.…”
Section: Introductionmentioning
confidence: 99%